Impact Of Early Childhood Sports Intervention on The Discovery of Physical Fitness Potential of Young Children: Jiang Xi Province - Wang, Lili; Pa , Wan Ahmad Munsif Bin Wan; Ling, Wang; Koh, Denise (Journal of Ecohumanism, 2024)
This study highlights the significance of forming lifelong physical activity habits at a young age by investigating the effects of early childhood sports intervention on young children’s capacity for physical fitness in Jiangxi Province, China. The study looks at physical strength, flexibility, coordination, and cardiovascular health using a quantitative methodology that includes surveys and objective evaluations. Partial Least Squares regression is used for analysis. The results show that sports intervention programmes have a positive impact on participants’ potential for physical fitness as well as their emotional, social, and cognitive development. While practical implications place an emphasis on policy integration and community partnerships, theoretical implications depend on a variety of theories to understand developmental outcomes. Nonetheless certain limitations, such as the cross-sectional design, the study offers insightful information about how sports intervention might promote children’s well-being and suggests future research directions to improve generalizability and deepen understanding.